Interactions of copper (II) chloride with sucrose, glucose, and fructose in aqueous solutions - Ribeiro, A. C. F. (2007)
The interaction between copper (II) chloride and the carbohydrates sucrose, glucose, and fructose has been studied in aqueous solutions at 298.15 and 310.15 K, using measurements of diffusion coefficients and electrical conductivity. Significant effects on the electrical conductivity were observed in the presence of these carbohydrates, suggesting interactions between them and copper chloride. Support for this came from diffusion coefficient measurements. These studies have been complemented by molecular mechanics calculations.